(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Massive changes in physicochemical composition and color variation usually occur in fruits during maturation and ripening. This study is conducted to implement an image processing system and develop a maturity color chart of banana. Actually, natural ripening color is different than impose ripening. Maturity color chart will help the consumer when it will be in the packet of banana. The earliest physiological maturity (stage-1) was marked as the stage when the flesh color was olive green and the pulp turning yellow and the subsequent maturity stages determined whenever changes the color as stage-2 (green smoke), stage-3 (apple green), stage-4 (olive drab), stage-5 (yellow) and stage-6 (golden rod) color. For each of the maturity stages, physical (peel color, firmness, and weight loss) and biochemical (anthocyanin content, carotenoids content, titrable acidity, pH, total soluble solids, ascorbic acid, reducing sugar, non-reducing sugar, and total sugar) maturity indices were determined. We had classified the maturity stages of banana based on the RGB (Red, Green, and Blue) and HSV (Hue, Saturation and Value) values. Average, median, minimum and maximum values were used in this study. After completing the qualitative analysis of RGB and HSV values we found the correlation coefficient of RGB and HSV values. The red color (R) values of bananas would increase when stages increase and the hue (H) means the pure color of bananas decreases when stages increase. Therefore, we can say that maturity stages of bananas mainly depend on R and H values. In case of Amritsagor banana at stage-6 (golden rod) color, TSS (Total Soluble Solid) (2.1%), TA (Titrable Acidity) (0.96%), pH (5.2), sugar (1.25%), vitamin C (2.5 mg/100g), reducing sugar (1.04%), non-reducing sugar (0.2%), anthocyanin (0.55 mg/100g) carotenoids (0.38 mg/100g) and at stage-1 (olive green) color, pH (6.8), vitamin C (8.75 mg/100g) are significantly highest. The results show that as maturation progressed, firmness decreased gradually and flesh color turned olive green to golden rod with ripening. Total soluble solids increased while TA (Titrable acidity) gradually increased with maturity. The results revealed that, there is a significant relationship between nutritional value, firmness and fruit skin color. So, the fruit of stage-1 (olive green) is suitable for harvesting and stages-6 (golden rod) color is suitable for consumption. Actually this message for grower/ owner or who would like to harvest and consumer. Fruit is banana, to observe the change of color keep it at room temperature. Neither artificial nor chemical system used here. Each and every box will carry the real maturity color chart. J. Bangladesh Agril. Univ. 16(2): 293-302, August 2018